Pathological Spectrum of Dura-Based Nonmeningothelial Lesions: 5 Years' Experience from a Tertiary Care Centre - Rao, Shilpa; Chandran, Chitra; Konar, Subhas; Mahadevan, Anita; Santosh, Vani; Nandeesh, B N. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Introduction Nonmeningothelial lesions arising from the dura comprise a wide spectrum of pathologies ranging from neoplastic to infective etiologies. They have overlapping clinical and radiologic findings necessitating histopathological evaluation for the final diagnosis which in turn dictates management and prognosis. Therapeutic strategies are different for each of the lesion. There is scarcity of large case series detailing clinicopathological spectrum of dura-based nonmeningothelial lesions.Materials and Methods In this study, we analyzed the neuropathological spectrum of dura-based nonmeningothelial lesions diagnosed over a period of 5 years in our tertiary care center.Results There were 79 cases of dura-based nonmeningothelial lesions constituting 7.3% of all dura-based lesions (age range: 2–75 years; M:F = 2:3). Basal region was more frequently involved than the convexities. On histopathology, neoplastic lesions predominated (92.4%) and included in order of frequency solitary fibrous tumor/hemangiopericytoma (35.6%), gliomas (27.4%), metastasis (27.4%), mesenchymal tumors (4%), primitive neuroectodermal tumor (2.73%), and medulloblastoma (2.73%). Infective lesions were less frequent (7.6%), included fungal infections and Rosai-Dorfman disease.Conclusion Awareness of the spectrum of nonmeningothelial dural lesions is useful for pathologists as well as the treating surgeon.
Keywords: Dura; nonmeningothelial; tumor; infection; pathology